Guidelines for the Management of Welfare for Disabled Workers to Promote Equal Rights and Freedoms: A Case Study of International Hotel Chains in the Bangkok - Taweephol, Rachanon; Jindachote, Prommatr; Mongkolnimit, Sabaithip; Maneerat, Sarayuth; Aiamssard, Chissanu (Research and Development Journal, Loei Rajabhat University, 2025)
This study aimed to: 1) investigate the limitations and obstacles experienced by disabled workers in international hotel chains; and 2) examine welfare management models developed for this workforce. A qualitative research methodology was adopted, utilizing a case study approach. Data were collected through in-depth interviews with 12 key informants, all of whom were human resource managers from 12 international hotel chains located in Bangkok. The findings revealed two key issues: 1) Disabled employees face challenges related to their physical condition, particularly among those with hearing impairments who rely on sign language for communication. In addition, most hotels lacked dedicated training programs tailored to the needs of disabled workers, and some had not yet implemented adequate accessibility accommodations within their premises; 2) The welfare management models emphasized equality with general employees, featuring training programs to support the professional development of disabled staff and measures to protect personal data in accordance with organizational privacy standards.